2004
DOI: 10.1038/sj.eye.6700718
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catalase activity and malondialdehyde level in patients with cataract

Abstract: Purpose Oxidative mechanisms play a major role in the aetiology and pathogenesis of cataract, especially in age-related cataract. Our study aims to investigate systemic oxidant and antioxidant markers in cataract patients. Methods The activity of erythrocyte catalase and the level of malondialdehyde in plasma were measured in 40 patients with cataract and 60 healthy control subjects. The malondialdehyde level, as an index of lipid peroxidation, was determined by thiobarbitü ric acid reaction according to Yagi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
3
20
0
3
Order By: Relevance
“…Earlier studies have reported increased levels of the lipid peroxidation product, MDA, in the cataract subjects as compared to those in the controls, which was in accordance with our findings [5,[10][11][12][13]. The high levels of TBARS in the cataractous lenses may, in turn, be the result of the lipid peroxidation of the lens cell membrane, which is produced locally or they may be the consequence of the migration of the products from the retina [14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…Earlier studies have reported increased levels of the lipid peroxidation product, MDA, in the cataract subjects as compared to those in the controls, which was in accordance with our findings [5,[10][11][12][13]. The high levels of TBARS in the cataractous lenses may, in turn, be the result of the lipid peroxidation of the lens cell membrane, which is produced locally or they may be the consequence of the migration of the products from the retina [14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…31 In the study of Katta AV et al, serum MDA (nmol/ml) values of Mean with SD was significantly higher in 60 patients of senile cataract with 30 cases of nuclear (5.14±1.0) and 30 cases of cortical (3.95±0.71) when compared with 30 normal controls (2.92±0.50). 32 Present study and the above studies showed that the increase in the level of serum MDA is directly related to the progression of the senile cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case-control studies were, however, inconclusive about the enrollment of systemic oxidative stress (6,10), and the possible reasons of the disturbed oxidant/antioxidant balance in SC (5,7,8,9,11). It has to be noted that the genesis of SC is of multiple origin, and some etiological risk factors, like visible and UV light exposure, have long-lasting but mostly local effects.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic oxidative stress in SC was previously associated with the decreased activities of superoxide dismutase (7), catalase (8), paraoxonase (9) and GST (11). The majority of blood hydroperoxides are, however, reduced by plasma GPx, and their efficient removal would thus diminish plasma MDA levels as well, as indicated in our study by the significant inverse correlations between plasma GPx, hydroperoxides and MDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation